Determinants of lost-to-follow-up (LTFU) among National Health Insurance Scheme-insured hypertension and diabetes patients attending accredited health facilities in Ghana - Edward Nketiah-Amponsah; Solomon Ahimah-Agyakwah; Robert Kaba Alhassan; Gifty Sunkwa-Mills; G. P. Gómez-Pérez; Judith van Andel; Alex Yao Israel Attachey; Yaw Nyarko Opoku-Boateng; Vivian Addo-Cobbiah; Bernard Okoe-Boye; Tobias Floris Rinke de Wit; Maxwell Akwasi Antwi (Tropical Medicine and Health)
Abstract Background Hypertension (HPT) and diabetes mellitus (DM) are major contributors to morbidity and mortality in Ghana. A key challenge in managing these conditions is non-adherence to follow-up visits, commonly referred to as "lost- to- follow-up" (LTFU). Data from the National Health Insurance Authority (NHIA) between 2017 and 2019 revealed that 37% (232,442/634,981) of patients were LTFU at NHIA-accredited health facilities. This study aimed to investigate the factors driving this high LTFU rate in Ghana. Methods A total of 480 hypertensive and diabetic patients, randomly selected from the NHIA electronic claims database from facilities in the Greater Accra and Ashanti regions between 2019 and 2020, were interviewed. Participants were divided into two groups: LTFU, which consisted of only one visit (351, 73%), and follow-up (FU), which consisted of more than one visit (129, 27%). The sample included patients diagnosed with hypertension only (308, 64%), diabetes only (45, 9%), and both hypertension and diabetes (127, 26%). Results No statistically significant socioeconomic differences were observed between the LTFU and FU groups, except in their adherence to follow-up visits. The likelihood of LTFU was higher among patients without follow-up awareness (OR = 2.5, 95% CI: 1.05–4.83), those who felt stigmatized (OR = 15.51, 95% CI: 1.01–238.90), those who attended facilities where physicians were available only some of the time (OR = 7.37, 95% CI: 1.07–50.61), those attending facilities without the necessary diagnostic equipment, those who described the NHIS coverage for DM diagnostic tests as inadequate, and those receiving traditional or herbal treatments (OR = 16.90, 95% CI: 3.12–91.45). Conversely, patients from the Ashanti Region (OR = 0.58, 95% CI: 0.35–0.96), those educated on diagnostic procedures (OR = 0.28, 95% CI: 0.08–0.98), and those whose treatment was not under control (OR = 0.04, 95% CI: 0.00–0.69) were less likely to be LTFU. Additionally, patients diagnosed more than ten years ago (OR = 0.44, 95% CI: 0.24–0.79) and those who were neutral about establishing support groups were less likely to be LTFU. Conclusions The study found that lack of follow-up awareness, stigmatization, and preference for traditional or herbal treatments are key drivers of lost-to-follow-up behavior among hypertension and diabetes patients. Thus, remedial policies should include increasing patient education on the importance of follow-up visits, ensuring the availability of essential medications, diagnostic equipment, and physicians, expanding the NHIA financial coverage, and integrating traditional medicine into standard healthcare to improve treatment adherence and reduce LTFU rates.